Organizational Justice: Providing a Model For Measuring External Organizational Justice - Seyed Yaghoub Hosseini; Samira Karimi (مطالعات مدیریت بهبود و تحول, 2012)
In the most of studies, organizational justice has been considered in connection with inside stakeholders. Due to consequences of Organizational Justice, it has become one of the most attractive research topics in the field of industrial and organizational psychology. Since External Organizational Justice has been researched a little, this study was conducted in line with this theoretical vacuum and with purpose of provide a model for assessing external organizational justice concept. As for the research objective, this study can be classified as an “applied research” while as for data gathering, it can be classified as a “descriptive” study with “correlation” strategy. Data collection tool was questionnaire, and the reliability of it was calculated by using of Cronbach's alpha, final value of Alpha was 0.81 which shows the higher liability of the questionnaire. To test the research hypotheses, structural equation modeling is used. The results show that identified dimensions (justice by costumer, justice in supplier, justice with competitors and environmental justice) measured the concept of external organizational Justice.